(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
The discovery of natural gas played very important role in economy. It effected the urbanization of different countries and changed the economic status in the world. The discovery of natural gas led to higher immigration, increased mobility between countries which in-turn affected the size of the population. Also, the revenue and wealth of different countries were greatly fluctuated with this discovery. Along with this effects, many vital events, services and support facilities were also improved all over the world. The data in our study shows different provinces population, wealth and natural gas. We will study whether natural gas has any affect on the growth of the population and total wealth.